2017
DOI: 10.2147/opto.s139651
|View full text |Cite
|
Sign up to set email alerts
|

Contact lens care tips for patients: an optometrist’s perspective

Abstract: Contact lens (CL) wear has been a viable alternative to spectacle wear for several decades. The interest and desire to wear CLs have been stable in recent years, evidenced by the consistency of new wearers into this category of refractive correction. CLs have become one of the most commonly used medical devices in the market, with more than 40 million wearers in the US. There are many activities in which patients report a preference of CL wear over spectacles (athletics for example). Nearly all patients (even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 48 publications
(87 reference statements)
2
33
0
1
Order By: Relevance
“…CLs are considered one of the most widely used medical devices globally and they require a prescription from an eyecare medical practitioner in many developed countries [9][10][11]. Nevertheless, CLs in many countries are sold without a prescription and obtained from various retailers such as optical stores, pharmacies, beauty salons, and over the internet [7,8,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLs are considered one of the most widely used medical devices globally and they require a prescription from an eyecare medical practitioner in many developed countries [9][10][11]. Nevertheless, CLs in many countries are sold without a prescription and obtained from various retailers such as optical stores, pharmacies, beauty salons, and over the internet [7,8,12].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advances in CL materials and the simplicity of care products, non-compliance to CL wear and care remains prevalent amongst wearers in many regions [ 9 , 18 ]. Many studies have investigated the level of compliance to CL wear and care, focusing on specific groups of CL wearers such as daily disposable (DD) CL wearers [ 21 ], females [ 7 ], or students [ 12 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, general hygiene is not only about keeping surfaces and surroundings clean, but it is also to give attention to the water source. In a review 22 on contact lens care tips, it is reported that only approximately 53–77% of contact lens wearing patients wash their hands before handling or insertion of their contact lenses. It is reported that the potential for infection can be reduced by 33% if there is good hand hygiene; keeping into account how often the hands of contact lens wearers come in contact with the face, make-up, face creams, possible nicotine and even dirt.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, a process is described where hand washing before lens insertion should change depending on how dirty the hands are. 22 The authors advocate the WHO method of hand washing and emphasize that washing with soap and water is enough as using alcohol-based rubs may damage the surface of the contact lens. Azuamah et al 23 conducted research relating to external eye diseases and personal hygiene among the patients visiting the optometry clinic in Owerri, Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in optometry research fields have made a substantial difference in a wide range of ophthalmological outcomes and the effectiveness of diagnostic and management challenges in a wide range of patient demographics. Research published in Clinical Optometry has improved our knowledge of how contact lenses impact the eye, for example their link with dry eye syndrome,1 and how we can improve contact lens outcomes in the future 2. Since launched in 2009, the journal has published both high-quality clinical reviews and peer-reviewed original research.…”
mentioning
confidence: 99%